Anti-O-specific polysaccharide (OSP) immune responses following vaccination with oral cholera vaccine CVD 103-HgR correlate with protection against cholera after infection with wild-type Vibrio cholerae O1 El Tor Inaba in North American volunteers. - Kamrul Islam; Motaher Hossain; Meagan Kelly; Leslie M Mayo Smith; Richelle C Charles; Taufiqur Rahman Bhuiyan; Pavol Kováč; Peng Xu; Regina C LaRocque; Stephen B Calderwood; Jakub K Simon; Wilbur H Chen; et al. (Public Library of Science (PLoS), 2018)
BACKGROUND:Cholera is an acute voluminous dehydrating diarrheal disease caused by toxigenic strains of Vibrio cholerae O1 and occasionally O139. A growing body of evidence indicates that immune responses targeting the O-specific polysaccharide (OSP) of V. cholerae are involved in mediating protection against cholera. We therefore assessed whether antibody responses against OSP occur after vaccination with live attenuated oral cholera vaccine CVD 103-HgR, and whether such responses correlate with protection against cholera. METHODOLOGY:We assessed adult North American volunteers (n = 46) who were vaccinated with 5 × 108 colony-forming units (CFU) of oral cholera vaccine CVD 103-HgR and then orally challenged with approximately 1 × 105 CFU of wild-type V. cholerae O1 El Tor Inaba strain N16961, either 10 or 90 days post-vaccination. PRINCIPAL FINDINGS:Vaccination was associated with induction of significant serum IgM and IgA anti-OSP and vibriocidal antibody responses within 10 days of vaccination. There was significant correlation between anti-OSP and vibriocidal antibody responses. IgM and IgA anti-OSP responses on day 10 following vaccination were associated with lower post-challenge stool volume (r = -0.44, P = 0.002; r = -0.36, P = 0.01; respectively), and none of 27 vaccinees who developed a ≥1.5 fold increase in any antibody isotype targeting OSP on day 10 following vaccination compared to baseline developed moderate or severe cholera following experimental challenge, while 5 of 19 who did not develop such anti-OSP responses did (P = 0.01). CONCLUSION:Oral vaccination with live attenuated cholera vaccine CVD 103-HgR induces antibodies that target V. cholerae OSP, and these anti-OSP responses correlate with protection against diarrhea following experimental challenge with V. cholerae O1. TRIAL REGISTRATION:ClinicalTrials.gov NCT01895855.